Influence of Gender, Race/Ethnicity & Socioeconomic Factors on Meniscus Treatment with Pediatric and Adolescent Acl Reconstruction. Issue 5 (31st May 2022) - Mercurio, Angela M.; Coene, Ryan P.; Cook, Danielle; Feldman, Lanna; Milewski, Matthew D.
Background: The rate of anterior cruciate ligament reconstruction (ACLR) in pediatric/adolescent populations has increased over time. However, there is less evidence to support the relative change in concomitant meniscus procedures over time. Demographics and socioeconomic (SES) factors may be implicated in the rate and usage of meniscectomy vs. meniscal repair as treatment. Hypothesis/Purpose: The purpose of this study is to assess if the rate of concomitant meniscus procedure with ACLR is increasing and what factors may be contributing to this rise. We hypothesize that age, sex, race/ethnicity, income, or insurance type may affect the rate of concomitant meniscus procedures. Methods: The Pediatric Health Information System (PHIS) Database was queried for all patients 18 years or younger who underwent ACLR with or without concomitant meniscus procedures based on CPT code from 2015-2019. Data from 39 out of 52 centers were included based on completeness of their data. Basic demographic information including age, sex, self-identified race/ethnicity, and insurance status was collected. Urban and rural designation was identified based on rural-urban commuting area (RUCA) codes. Based on the 2015 Department Health & Human Services Federal Poverty Guidelines (FPL), patients were stratified into lower (≤199% of FPL) and higher (≥200% of FPL) income brackets. Linear regression was used to model trends and multiple logistic regression modeling was used to test for associations. Results: 14, 398 patients underwent ACLR during the study period with 8, 337 patients (58%) having concomitant meniscal procedures with a 1.24-fold increase over five years (Figure 1). Of the 8, 337 patients with concomitant meniscus treatment, 46% had a meniscectomy and 54% had a meniscus repair. There was a 0.86-fold change in meniscectomy and a 1.70-fold increase in meniscus repair during the study period (Figure 2). Males, older patients, Black race, living in an urban area, and those with non-private insurance had increased odds of undergoing a concomitant meniscus procedure (all p<0.05). Patients of Black or other race and those with non-private insurance had increased odds of having a meniscectomy vs. meniscus repair (all p≤0.01). There were no associations detected between income bracket and our outcomes. Conclusions: This study shows that in pediatric and adolescent patients undergoing ACLR, there is a rise in concomitant meniscus procedures from 2015-2019. In addition, patients of non-white race and those with non-private insurance have increased odds of undergoing meniscectomy vs. meniscus repair. This study identifies access and inequality issues in ACLR with concomitant meniscus procedures in pediatric and adolescent populations. Figure 1. ACL Reconstruction vs ACL Reconstruction with Concomitant Meniscus Procedures from 2015-2019 Figure 2. ACL Reconstruction with Concomitant Meniscus Procedures: Meniscectomy vs. Meniscus Repair